Bracing of Beams, Trusses, and Joist Girders Using Open Web Steel Joists - Fisher, James M. (Engineering Journal, 2006)
Designers typically use joists as a part of the lateral bracing for the compression flange of beams, or for the lateral bracing of the top chord of trusses and joist girders. Joists serve as the connection to the primary members to deliver the brace force to a diaphragm or horizontal bracing system. The attachment of the joist seat to the primary member is an important element of the bracing system. Traditionally joist seats have been attached to primary members (beams, trusses, and joist girders) by welding. The OSHA Steel Erection Standard, Part 1926.757 - Open Web Steel Joists states: (i) Except for steel joists that have been pre-assembled into panels, connections of individual steel joists to steel structures in bays of 40 ft (12.2 m) or more shall be fabricated to allow for field bolting during erection; (ii) These connections shall be field-bolted unless constructability does not allow. The purpose of this paper is to discuss possible alternatives to welding the joists to the primary members in order to provide bracing to the primary members.